The next chapter reimagining the city library as an interactive community hub in the new normal - Leonida, Rafaella Alesna (College of Architecture, University of the Philippines Diliman, 2023)
Throughout history, city libraries have aided in providing universal access to information, constantly evolving in form and program to suit changing social contexts. New city library designs, integrating digital technology and diverse programs, have been developed to reimagine the typology within the context of modern society as an information center and as a third place. The COVID-19 pandemic introduced an altered social context known as the “new normal” defined by the prioritization of individual health and heightened dependence on digital technology. The new social context is expected to extend beyond the imminent end of the pandemic, characterized by altered interpersonal relationships and experiences of space. To further explore the city library typology and determine its role in the “new normal,” this study reevaluates the city library and proposes new spatial configurations with focus on the Philippine context. From data collected through a literature review, fieldwork, and key informant interviews, this study first proposes a building typology that supports the city library’s function as a third place and information center followed by library design guidelines for the new normal. The application of these to an architectural project is presented through the design of a city library in Mandaue City, Cebu. Overall, this study aims to contribute to the development of the city library typology in the Philippines through reimagining the city library as an interactive community hub capable of enlightening and empowering communities in the new normal.